Perancangan Basis Data Sistem Informasi Akademik SMK Swakarya Palembang - Meidyan Permata Putri; Evan Apriadi; Dimas Budi Asmoro (Teknomatika, 2019)
This research is intended to be approved by the Academic Information System database system. The implications of this design can be used to produce a web-based Swakarya Vocational Academic Information System. The database design of this website uses the Database Life Cycle (DBLC) method which produces 34 (thirty four) tables, namely Users, Students, religion, absent_students, absent_guru, teachers, forum_komentar, building, forum_topic, groups, identity_school, schedule_pelajaran, Jenis_Kelamin, Jenis_Kelamin, , Attendance, Class, Basic Competence, Curriculum, subject matter, key values, room, quizzes, quiz test categories, essay questions, essay answers, objective goals, objective objectives, objective topics, forum comments, elearning, elearning answers, elearning categories, desire questions , questions, accountability using conceptual, logical and physical.